2018
DOI: 10.3892/or.2018.6720
|View full text |Cite
|
Sign up to set email alerts
|

TCGA dataset‑based construction and integrated analysis of aberrantly expressed long non‑coding RNA mediated competing endogenous RNA network in gastric cancer

Abstract: The aberrant expression of long non-coding RNAs (lncRNAs) has been confirmed to play a pivotal role in tumor initiation and development. LncRNAs can interact with microRNAs (miRNAs) as competing endogenous RNAs (ceRNAs) to regulate the expression of target genes in various cancers. In the present study, the authors investigated the functions of lncRNAs as ceRNAs in gastric cancer (GC) and their implications for the prognosis. The RNA sequencing profiles of 372 tumor samples and 32 adjacent non-tumor gastric sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Studies have shown that lncRNA is essential in many biological processes including the regulation of the cell cycle and cell differentiation, the dose compensation effect and epigenetic regulation, making it a hot research subject in genetics [6]. In recent years, emerging evidence has shown that R e t r a c t e d lncRNA plays an important role in tumorigenesis and tumour development, including gastric adenocarcinoma [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that lncRNA is essential in many biological processes including the regulation of the cell cycle and cell differentiation, the dose compensation effect and epigenetic regulation, making it a hot research subject in genetics [6]. In recent years, emerging evidence has shown that R e t r a c t e d lncRNA plays an important role in tumorigenesis and tumour development, including gastric adenocarcinoma [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Fan et al reported that LINC00221 is upregulated in breast cancer compared to adjacent-normal breast tissues and is involved in the lncRNA–miRNA–mRNA ceRNA network of breast cancer [31]. He et al demonstrated that LINC00221 is dysregulated in gastric cancer and competes with six miRNAs (hsa‑miR‑96, hsa‑miR‑143, hsa‑miR‑204, hsa‑miR‑372, hsa‑miR‑373 and hsa‑miR‑519d) to mediate target mRNA expression in gastric cancer [32]. Zhang et al found that LINC00221 is associated with a poor prognosis in patients with gastric cancer, and an 11‑lncRNA signature consisting of LINC00221 can predict the survival rate for gastric cancer [33].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been carried out on the construction of ceRNA networks for gastric cancer which majorly focused on certain lncRNAs, and were not experimentally validated (8, 11, 13, 14). Our study emphasizes the establishment of a regulatory network rather than analyzing individual genes.…”
Section: Discussionmentioning
confidence: 99%